The crimson fairy book - Ford, H. J. (Henry Justice), 1860-1941; Lang, Andrew, 1844-1912 (New York : Dover Publications, 1967)
Thirty-six fairy tales from the folklore of Hungary, Russia, Rumania, Finland, Iceland, Japan, and Sicily
"Unabridged republication of the work originally published ... in 1903."
Keywords: Fairy tales; Folklore